Some aspects regarding the professional situation of female and male Jewish teachers in the interwar Polish public elementary education system as presented in the “Życie nauczycielskie” periodical (1926–1939) - Piotrowska-Marchewa, Monika (Instytut Historii Nauki im. Ludwika i Aleksandra Birkenmajerów Polskiej Akademii Nauk, 2022)
This paper presents a characteristic of the Życie nauczycielskie (Teacher’s Life) periodical: the bulletin of the Professional Association of Poland’s Elementary School Teachers (Polish: Zawodowe Zrzeszenie Nauczycielstwa Szkół Powszechnych Rzeczypospolitej Polskiej, 1926–1939). This association of Jewish teachers active in Polish public elementary schools has not, until now, been an object of detailed studies. Życie nauczycielskie, with socialist activist Ludwika Sachsowa as editor-in-chief, was a platform or the exchange of ideas and experiences between teachers working in Jewish schools, colloquially called “szabasówki”. Today, it can be considered an interesting, if somewhat forgotten, voice of a circle of secular, mostly female teachers espousing predominantly the political ideas of the democratic left . The periodical’s contents also serve to illustrate the realities of this acculturated social and professional group’s functioning: under conditions of increasingly assimilative tendencies of the educational policies of Poland’s authoritarian interwar Sanation regime and the strained Polish-Jewish relations on the precipice of World War II.
Keywords: Gustaw Butlow; Ludwika Sachsowa; acculturation of the Jews; assimilation; Central Jewish School Organisation; male Jewish teachers; female Jewish teachers; Polish Association of Freethinkers (PAF); Professional Association of Poland’s Elementary School Teachers; Professional Association of Teachers of Jewish Schools in Poland; public elementary education for national minorities of the Second Republic of Poland